A likelihood ratio like permutation test for one way designs. Issue 3 (3rd July 2017) - Samonenko, Inga; Robinson, John
ABSTRACT: We consider permutation tests based on a likelihood ratio like statistic for the one way or k sample design used in an example in Kolassa and Robinson [(2011), 'Saddlepoint Approximations for Likelihood Ratio Like Statistics with Applications to Permutation Tests', Annals of Statistics, 39, 3357–3368]. We give explicitly the region in which the statistic exists, obtaining results which permit calculation of the statistic on the boundary of this region. Numerical examples are given to illustrate improvement in the power of the tests compared to the classical statistics for long-tailed error distributions and no loss of power for normal error distributions.